(16 intermediate revisions by 4 users not shown)
Line 1: Line 1:
= Practice Question 1, [[ECE438]] Fall 2010, [[User:Mboutin|Prof. Boutin]] =
+
[[Category:problem solving]]
On Computing the DFT of a discrete-time periodic signal
+
[[Category:ECE438]]
 +
[[Category:discrete Fourier transform]]
 +
 
 +
<center><font size= 4>
 +
'''[[Digital_signal_processing_practice_problems_list|Practice Question on "Digital Signal Processing"]]'''
 +
</font size>
 +
 
 +
Topic: Discrete Fourier Transform
 +
 
 +
(On Computing the DFT of a discrete-time periodic signal.)
 +
</center>
 
----
 
----
 +
==Question==
 
Compute the discrete Fourier transform of the discrete-time signal  
 
Compute the discrete Fourier transform of the discrete-time signal  
  
Line 9: Line 20:
 
----
 
----
 
Post Your answer/questions below.
 
Post Your answer/questions below.
 
+
----
 +
==Answer 1==
 
<math>X [k] = \sum_{k=0}^{N-1} x[n].e^{-j.2\pi k n/N}</math>
 
<math>X [k] = \sum_{k=0}^{N-1} x[n].e^{-j.2\pi k n/N}</math>
  
Line 19: Line 31:
  
 
<math> X [k] = 1+ e^{-j(1)(\frac{2}{3}\pi)(1+k)} +e^{-j\frac{4}{3}\pi(1+k)}</math> <span style="color:green"> This gives you a very complicated answer. -pm </span>
 
<math> X [k] = 1+ e^{-j(1)(\frac{2}{3}\pi)(1+k)} +e^{-j\frac{4}{3}\pi(1+k)}</math> <span style="color:green"> This gives you a very complicated answer. -pm </span>
 +
 +
<math> X [0] = 1+ e^{-j(\frac{2}{3}\pi)(1+0)} +e^{-j\frac{4}{3}\pi(1+0)}</math>
 +
 +
<math> X [0] = 1+ e^{-j(\frac{2}{3}\pi)} +e^{-j(\frac{4}{3}\pi)}</math>
 +
 +
complex result: Noting <math>-2/3\pi</math> and <math>-4/3\pi</math> are conjugates cancel the imaginary component.
 +
 +
<math> 1+cos(-2/3\pi) +cos(-4/3\pi) = X[0] = 0 </math>
 +
 +
<math> X [1] = 1+ e^{-j(\frac{2}{3}\pi)(1+1)} +e^{-j\frac{4}{3}\pi(1+1)}</math>
 +
 +
<math> X [1] = 1+ e^{-j(\frac{4}{3}\pi)} +e^{-j\frac{8}{3}\pi}</math>
 +
 +
complex result: Noting <math>-4/3\pi</math> and <math>-8/3\pi</math> are conjugates cancel the imaginary component.
 +
 +
<math> 1+cos(-4/3\pi) +cos(-8/3\pi) = X[1] = 0</math>
 +
 +
<math> X [2] = 1+ e^{-j(\frac{2}{3}\pi)(1+2)} +e^{-j\frac{4}{3}\pi(1+2)}</math>
 +
 +
<math> X [2] = 1+ e^{-j(2\pi)} +e^{-j(4\pi)}</math>
 +
 +
<math> X [2] = 1+ 1 + 1 = 3</math>
 +
  
 
- AJFunche <span style="color:green"> Nice effort! -pm----
 
- AJFunche <span style="color:green"> Nice effort! -pm----
 
----
 
----
 +
==Answer 2==
 
<math>x[n] = \frac{1}{N}\sum_{k=0}^{N-1} X[k]e^{j2\pi k\frac{n}{N}}</math>
 
<math>x[n] = \frac{1}{N}\sum_{k=0}^{N-1} X[k]e^{j2\pi k\frac{n}{N}}</math>
  
 
<math>x[n] = \frac{1}{3}\sum_{k=0}^{2} X[k]e^{j\frac{2\pi}{3}kn}</math>
 
<math>x[n] = \frac{1}{3}\sum_{k=0}^{2} X[k]e^{j\frac{2\pi}{3}kn}</math>
  
<math>x[n] = \frac{1}{3} \cdot (X[0] + X[1]e^{j(\frac{2\pi}{3}n + 2\pi)} + X[2]e^{j(\frac{2\pi}{3}(2)n + 2\pi)})</math>  
+
<math>x[n] = \frac{1}{3} \cdot (X[0] + X[1]e^{j(\frac{2\pi}{3}(1)n )} + X[2]e^{j(\frac{2\pi}{3}(2)n)})</math>  
 
:<span style="color:green"> Notice that all the powers of e in this expression are positive, but the signal x[n] is expressed as a negative power of e, so you cannot compare just yet. -pm </span>
 
:<span style="color:green"> Notice that all the powers of e in this expression are positive, but the signal x[n] is expressed as a negative power of e, so you cannot compare just yet. -pm </span>
  
Line 44: Line 80:
 
Now compare with the inverse DFT formula.
 
Now compare with the inverse DFT formula.
  
<math>x[n] =... </math>  
+
<math>e^{j 2 \frac{2\pi n }{3} } \ \ compare \ with \ \  \frac{1}{3} \cdot (X[0] + X[1]e^{j(\frac{2\pi}{3}n)} + X[2]e^{j(\frac{2\pi}{3}(2)n)})</math>  
  
please continue. -pm
+
X[0] = 0
  
+
X[1] = 0
 +
 
 +
X[2] = 3
 
----
 
----
 +
==Answer 3==
 +
This could easily be shown that due to the modulation property that this is a shifted delta in the DFT world.
 +
But to do a little mathematical proof....
 +
<math>
 +
\begin{align}
 +
X [k] &= \sum_{n=0}^{N-1} x[n]e^{\frac{-j2\pi k n}{N}} \\
 +
&= \sum_{n=0}^{N-1} e^{-j\frac{2}{3}\pi n}e^{\frac{-j2\pi k n}{N}} \text{ where N=3 because of periodicity of the signal} \\
 +
&= \sum_{n=0}^{2} e^{j\frac{4}{3}\pi n}e^{-j \frac{2}{3} \pi n k} \\
 +
&= \sum_{n=0}^{2} e^{-j\frac{2}{3}\pi n (k-2)}
 +
\end{align}
 +
</math>
  
*Answer/question
+
Now to get the final result you must compare this equation to the IDFT formula and you get that
 +
 
 +
<math>
 +
\begin{align}
 +
X [k] &= \sum_{n=0}^{N-1} x[n]e^{\frac{-j2\pi k n}{N}} &= 3 \delta (k-2)
 +
\end{align}
 +
</math>
 +
 
 +
In class we compared the IDFT and the Fourier Series expansion and the Fourier coefficients can be expressed (if I remember correctly) as
 +
 
 +
<math >
 +
A_{k}= \frac{X[k]}{N}
 +
</math>
 +
 
 +
:<span style="color:purple"> This is a different and interesting way of looking at the problem. -pm----
 +
 
 +
:<span style="color:green"> But does that mean my solution is wrong or just unique...? - my
 +
----
 
*Answer/question
 
*Answer/question
 
----
 
----

Latest revision as of 14:22, 21 April 2013


Practice Question on "Digital Signal Processing"

Topic: Discrete Fourier Transform

(On Computing the DFT of a discrete-time periodic signal.)


Question

Compute the discrete Fourier transform of the discrete-time signal

$ x[n]= e^{-j \frac{2}{3} \pi n} $.

How does your answer related to the Fourier series coefficients of x[n]?


Post Your answer/questions below.


Answer 1

$ X [k] = \sum_{k=0}^{N-1} x[n].e^{-j.2\pi k n/N} $

$ N=3 $ That's correct! -pm

$ x[n]= e^{-j \frac{2}{3} \pi n} $

$ X [k] = \sum_{k=0}^{2}e^{-j(n)(\frac{2}{3}\pi)(1+k)} $ You are using the long route, instead of the short route. -pm

$ X [k] = 1+ e^{-j(1)(\frac{2}{3}\pi)(1+k)} +e^{-j\frac{4}{3}\pi(1+k)} $ This gives you a very complicated answer. -pm

$ X [0] = 1+ e^{-j(\frac{2}{3}\pi)(1+0)} +e^{-j\frac{4}{3}\pi(1+0)} $

$ X [0] = 1+ e^{-j(\frac{2}{3}\pi)} +e^{-j(\frac{4}{3}\pi)} $

complex result: Noting $ -2/3\pi $ and $ -4/3\pi $ are conjugates cancel the imaginary component.

$ 1+cos(-2/3\pi) +cos(-4/3\pi) = X[0] = 0 $

$ X [1] = 1+ e^{-j(\frac{2}{3}\pi)(1+1)} +e^{-j\frac{4}{3}\pi(1+1)} $

$ X [1] = 1+ e^{-j(\frac{4}{3}\pi)} +e^{-j\frac{8}{3}\pi} $

complex result: Noting $ -4/3\pi $ and $ -8/3\pi $ are conjugates cancel the imaginary component.

$ 1+cos(-4/3\pi) +cos(-8/3\pi) = X[1] = 0 $

$ X [2] = 1+ e^{-j(\frac{2}{3}\pi)(1+2)} +e^{-j\frac{4}{3}\pi(1+2)} $

$ X [2] = 1+ e^{-j(2\pi)} +e^{-j(4\pi)} $

$ X [2] = 1+ 1 + 1 = 3 $


- AJFunche Nice effort! -pm----


Answer 2

$ x[n] = \frac{1}{N}\sum_{k=0}^{N-1} X[k]e^{j2\pi k\frac{n}{N}} $

$ x[n] = \frac{1}{3}\sum_{k=0}^{2} X[k]e^{j\frac{2\pi}{3}kn} $

$ x[n] = \frac{1}{3} \cdot (X[0] + X[1]e^{j(\frac{2\pi}{3}(1)n )} + X[2]e^{j(\frac{2\pi}{3}(2)n)}) $

Notice that all the powers of e in this expression are positive, but the signal x[n] is expressed as a negative power of e, so you cannot compare just yet. -pm

whoops, I was doing the homework. is that correct? - ksoong

Tecnically yes, but not realy useful for computing the DFT. Instead, use the fact that $ e^{ 2 \pi n j}=1 $ to rewrite x[n] as a positive power of e. (Just add $ 2 \pi n j $ to the exponent of e). -pm

$ \begin{align} x[n]&= e^{-j \frac{2}{3} \pi n} \\ &= e^{-j \frac{2}{3} \pi n} e^{j 2 \pi n} \text{ (since this is the same as multiplying by one, for any integer n)}\\ &= e^{-j \frac{2}{3} \pi n +j 2 \pi n } \\ & = e^{j \frac{4}{3} \pi n} \\ & = e^{j 2 \frac{2\pi n }{3} } \end{align} $

Now compare with the inverse DFT formula.

$ e^{j 2 \frac{2\pi n }{3} } \ \ compare \ with \ \ \frac{1}{3} \cdot (X[0] + X[1]e^{j(\frac{2\pi}{3}n)} + X[2]e^{j(\frac{2\pi}{3}(2)n)}) $

X[0] = 0

X[1] = 0

X[2] = 3


Answer 3

This could easily be shown that due to the modulation property that this is a shifted delta in the DFT world. But to do a little mathematical proof.... $ \begin{align} X [k] &= \sum_{n=0}^{N-1} x[n]e^{\frac{-j2\pi k n}{N}} \\ &= \sum_{n=0}^{N-1} e^{-j\frac{2}{3}\pi n}e^{\frac{-j2\pi k n}{N}} \text{ where N=3 because of periodicity of the signal} \\ &= \sum_{n=0}^{2} e^{j\frac{4}{3}\pi n}e^{-j \frac{2}{3} \pi n k} \\ &= \sum_{n=0}^{2} e^{-j\frac{2}{3}\pi n (k-2)} \end{align} $

Now to get the final result you must compare this equation to the IDFT formula and you get that

$ \begin{align} X [k] &= \sum_{n=0}^{N-1} x[n]e^{\frac{-j2\pi k n}{N}} &= 3 \delta (k-2) \end{align} $

In class we compared the IDFT and the Fourier Series expansion and the Fourier coefficients can be expressed (if I remember correctly) as

$ A_{k}= \frac{X[k]}{N} $

This is a different and interesting way of looking at the problem. -pm----
But does that mean my solution is wrong or just unique...? - my

  • Answer/question

Next practice problem


Back to 2010 Fall ECE 438 Boutin

Alumni Liaison

Ph.D. on Applied Mathematics in Aug 2007. Involved on applications of image super-resolution to electron microscopy

Francisco Blanco-Silva